CLICK, CLACK, MOO Cows That Type - Cronin, Doreen; Lewin, Betsy; SENSEE (California : SENSEE, 2021)
A bunch of literate cows go on strike after Farmer Brown refuses to give in to their demands of electric blankets when the barn gets too cold. "Cows that type. Hens on strike!" How will Farmer Brown resolve his problems?
Braille Books
This book was made for those with visual impairment.
Tactile materials
Caldecott Honor Book
Keywords: Cows -- Juvenile fiction; Animals. -- Juvenile fiction; Children's stories; Braille Books; Picture books